2018
DOI: 10.1128/jb.00527-18
|View full text |Cite
|
Sign up to set email alerts
|

The Di-iron RIC Protein (YtfE) of Escherichia coli Interacts with the DNA-Binding Protein from Starved Cells (Dps) To Diminish RIC Protein-Mediated Redox Stress

Abstract: The RIC (repair of iron clusters) protein of Escherichia coli is a di-iron hemerythrin-like protein that has a proposed function in repairing stress-damaged iron-sulfur clusters. In this work, we performed a bacterial two-hybrid screening to search for RIC-protein interaction partners in E. coli. As a result, the DNA-binding protein from starved cells (Dps) was identified, and its potential interaction with RIC was tested by bacterial adenylate cyclase-based two-hybrid (BACTH) system, bimolecular fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Upregulation of ytfE following hydrogen peroxide-mediated damage of Staphylococcus aureus indicates that YtfE may play a broad role in repair, instead of just a response to nitrogen stress (44, 45). Additional studies in E. coli also suggest that YtfE repairs Fe-S cluster proteins damaged by hydrogen peroxide (13, 46-49).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ytfE following hydrogen peroxide-mediated damage of Staphylococcus aureus indicates that YtfE may play a broad role in repair, instead of just a response to nitrogen stress (44, 45). Additional studies in E. coli also suggest that YtfE repairs Fe-S cluster proteins damaged by hydrogen peroxide (13, 46-49).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies in E. coli also suggest that YtfE repairs Fe-S cluster proteins damaged by hydrogen peroxide (13, 4649).…”
Section: Discussionmentioning
confidence: 99%
“…The mononuclear iron YtfE-E159L mimics an YtfE protein following iron release and its structure shows that the process implies the movement of one of the axial histidines that exposes the metal site cavity to the exterior, thus making possible the re-entry of another iron atom to rebuild the di-iron center. Since we previously showed that YtfE interacts with E. coli Dps (DNA-binding Protein from Starved cells; Silva L.S.O. et al, 2018 ), we may hypothesize that this iron storage protein constitutes a good candidate to promote the reconstitution of the di-iron cluster in YtfE.…”
Section: Discussionmentioning
confidence: 99%
“…After 5 h, the cross-linking agent formaldehyde (1% final concentration) was added. Incubation proceeded at 37°C for 20 min, and the reaction was stopped by incubation with 0.5 M glycine at room temperature for 5 min ( Silva L.S.O. et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%